High voltage and electrical insulation engineering - Arora, Ravindra; Mosch, Wolfgang (IEEE Press series on power engineering, 2010)
The book is written for students as well as for teachers and researchers in the field of High Voltage and Insulation Engineering. It is based on the advance level courses conducted at TU Dresden, Germany and Indian Institute of Technology Kanpur, India. The book has a novel approach describing the fundamental concept of field dependent behavior of dielectrics subjected to high voltage.